FORMULASI STRATEGI BERSAING TERMINAL PETI KEMAS PADA MAKASSAR NEW PORT - Abbas; Dianita Veronica Lantang; Hardiyono (Paulus Journal of Accounting (PJA), 2024)
This study aims to analyze the Competitive Strategy Formulation of Container Terminals at Makassar New Port. This type of research uses a qualitative approach. This research is an exploratory type of research by identifying and developing Porter's 5 forces strategy. Data analysis conducted in this study is internal and external environmental analysis, TOWS analysis and Porter's 5 Forces in addition to the use of SWOT analysis to analyze the company's internal factors so that it can be known what factors are the strengths and weaknesses. The results of the study indicate that an effective strategy for developing container competitiveness by relying on a strategic location to support container activities and services will make it easier for companies to increase container flow because it is supported by various government regulations and regulations, adding Container Crane Twin Lift equipment to increase productivity, increase the accuracy of container activities, and capital competence and professionalism of HR owned by the company.